Emerging horizons for tick-borne pathogens: from the 'one pathogen–one disease' vision to the pathobiome paradigm. (December 2015) - Vayssier-Taussat, Muriel; Kazimirova, Maria; Hubalek, Zdenek; Hornok, Sándor; Farkas, Robert; Cosson, Jean-François; Bonnet, Sarah; Vourch, Gwenaël; Gasqui, Patrick; Mihalca, Andrei Daniel; Plantard, Olivier; Silaghi, Cornelia; et al.
Ticks, as vectors of several notorious zoonotic pathogens, represent an important and increasing threat for human and animal health in Europe. Recent applications of new technology revealed the complexity of the tick microbiome, which may affect its vectorial capacity. Appreciation of these complex systems is expanding our understanding of tick-borne pathogens, leading us to evolve a more integrated view that embraces the 'pathobiome'; the pathogenic agent integrated within its abiotic and biotic environments. In this review, we will explore how this new vision will revolutionize our understanding of tick-borne diseases. We will discuss the implications in terms of future research approaches that will enable us to efficiently prevent and control the threat posed by ticks.